AMELIORASI LIMBAH CUCIAN BERAS DAN CANGKANG TELUR AYAM TERHADAP TANAMAN CABAI RAWIT (Capsicum frustescens L.) - Roefaida, Effy -; Raja Kana, Yenny; Gandut, Yosefina R. Y; Oematan, Shirly S; Bunga, Widasari; Maha Kati, Thomas U. P (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Management of household waste such as rice washing water waste and eggshell waste needs to be continuously encouraged to add value to useless items and overcome environmental problems. Rice washing water and eggshell waste have content that is beneficial for plant growth and development, so they can be made as organic fertilizer. Organic fertilizer from washing water waste as a substitute for organic fertilizer can increase plant productivity and eggshell waste can also be used for making organic fertilizer because it contains Potassium, Calcium, Phosphorus and Magnesium. Organic fertilization is an alternative to improve soil properties and increase growth and yield of cayenne pepper. This study aims to determine the effect of the combination of rice washing waste and chicken eggshells on cayenne pepper plants. The study was designed using a completely randomized design (CRD). The combination treatment consisted of 10 treatments which were repeated 8 times. The combination of giving washing water with chicken egg shells is as follows: The combination of liquid waste with a concentration of 0 ml/L of water and egg shell waste of 0 grams (control); Combination of rice washing waste with a concentration of 300 ml/L of water and 15 grams of eggshell waste; The combination of rice washing waste with a concentration of 400 ml/L of water and 15 grams of eggshell waste; The combination of rice washing waste with a concentration of 500 ml/L of water and 15 grams of eggshell waste; Combination of rice washing waste with a concentration of 300 ml/L of water and 20 grams of eggshell waste; Combination of rice washing waste with a concentration of 400 ml/L of water and 20 grams of eggshell waste; Combination of rice washing waste with a concentration of 500 ml/L of water and 20 grams of eggshell waste; Combination of rice washing waste with a concentration of 300 ml/L of water and 25 grams of eggshell waste; Combination of rice washing waste with a concentration of 400 ml/L of water and 25 grams of eggshell waste; The combination of rice washing waste with a concentration of 500 ml/L of water and 25 grams of eggshell waste. observational variables, namely the increase in plant height (cm); Number of productive branches; Number of fruits per plant and total weight of fresh fruit per plant (g). The results showed that the combination of rice washing water waste 400 ml/L of water and 20 grams of chicken eggshells could increase the yield of the best crop for the number of fruits per plant, namely 45.25 and the total weight of harvested fruit per plant was 25.13 grams of cayenne pepper.